2019
DOI: 10.2478/fon-2019-0008
|View full text |Cite
|
Sign up to set email alerts
|

Critical emancipatory reflection on a practice-based issue in relation to nurses’ communicative role with unsatisfied clients in Chinese hospitals

Abstract: ObjectiveThis study aims to use reflective theory and critical emancipatory theory to explore nurses’ communicative role with unsatisfied clients.MethodsThis paper begins with the broad issue, and the analysis will engage Smyth’s cycle, which includes describing, analyzing, exploring, and reconstructing.ResultsCritical emancipatory reflection is essential to make changes in the professional practice of nursing, because it is of primary importance for the professional learning and development of a nurse.Conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…58,59 Although reflection and self-awareness are key components of contemporary nurse education programs in the ROI, many nurses in this study were not confident with these areas and they did not rank them highly in terms of importance. This is interesting as it is generally accepted that reflective learning by nurses in health care needs to be increased 3,60 and that reflective practice education, and supervision for reflective practice needs to be encouraged. 61 Reflection has been found to be a useful way of reframing incidents of poor communication and developing new insights that can improve personal practice.…”
Section: Itemsmentioning
confidence: 99%
See 2 more Smart Citations
“…58,59 Although reflection and self-awareness are key components of contemporary nurse education programs in the ROI, many nurses in this study were not confident with these areas and they did not rank them highly in terms of importance. This is interesting as it is generally accepted that reflective learning by nurses in health care needs to be increased 3,60 and that reflective practice education, and supervision for reflective practice needs to be encouraged. 61 Reflection has been found to be a useful way of reframing incidents of poor communication and developing new insights that can improve personal practice.…”
Section: Itemsmentioning
confidence: 99%
“…2 Families are vulnerable and their responses to inadequacies, including perceptions of communication, can be very negative. 3 Indeed almost a decade ago Bail 4 published a literature review in this journal motivated by "a frustration working in an acute health care system where processes can appear more valued than the people they are meant to benefit." Bail's review 4 found widespread patient dissatisfaction with health care communication, in particular health care and technological support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Frustrations can arise if this is not the case, as families perceive inadequacies in care and may complain. 30 However, when nurses transform the patient's room into a peaceful and home-like atmosphere for example, this can make a tremendous difference to the feeling of comfort, improve the families' psychosocial wellbeing, though these matters are not costly. 17 Of course, supportive interventions by the nurse are more effective when the nurse is experienced and skilled in technical competence and human competence.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are encouraged in these circumstances to reflect on their personal practice and consider ways so that it could be improved. 30,31 It is possible for example to determine what more could be done in personal practice to display comfort, or build trust, and having the capacity to reflect and learn from this reflection is crucial. 31 The World Health Organization 32 recommends that patients at the end-of-life stage should have a high quality of life mediated by comfort care including comprehensive intervention for pain and other physical and psychosocial needs.…”
Section: Model Casementioning
confidence: 99%